Analysis of Inventory Control of Perishable Goods with Capital Constraints and Warehouse Capacity Using the Lagrange EOQ Method (Case Study UD. XYZ) - Ahmad Taufiqur Rahman; Dzakiyah Widyaningrum (Advance Sustainable Science Engineering and Technology, 2023)
Inventory control is a company policy in managing goods in order to optimize the number of orders and minimize inventory costs. The object of this research is PT XYZ in Gresik city which produces tempeh and tofu. Several raw materials are needed in the production process, one of which is soybeans. As the main raw material for making tempeh and tofu, soybeans are perishable goods. Previously, the company used a method based on past usage data in controlling its inventory, resulting in bloated inventory costs and a buildup of raw materials in the warehouse. Therefore, researchers need a method that is economical and takes into account the limitations of the company. The Lagrange EOQ method is a model that measures the order quantity by looking at one or more restrictions. The results of the Lagrange EOQ method get an order quantity of 20 sacks of soybeans with an order frequency of 27 times a year, a total inventory cost of Rp. 665,575, an ROP of 12 sacks and a safety stock of 10 sacks.